Complete response to immunotherapy in sinonasal undifferentiated carcinoma. Issue 6 (December 2021) - Denaro, Nerina; Merlano, Marco; Numico, Gianmauro; Garrone, Ornella; Bossi, Paolo
Sinonasal undifferentiated carcinoma (SNUC) is an uncommon aggressive tumor. Locally advanced disease is usually diagnosed at presentation. Multidisciplinary approach is essential and aims to ensure optimal trimodal strategy. Induction chemotherapy is preferred in order to select patients who will benefit from chemoradiotherapy or surgery. Immunotherapy is not indicated in patients with recurrent SNUC. We describe an impressive response in a young man previously treated with radiotherapy and chemotherapy and demolitive surgery who had metastatic bone and lung disease. We also report data on PD-L1, next-generation sequencing, and neutrophil/platelets ratio.